Status Hukum Pulau Pasir Oleh Autralia Berkaitan Dengan Kegiatan Nelayan Tradisional Indonesia Berdasarkan United Nation Convention On The Law Of The Sea (UNCLOS) 1982 - Marni Agustina Dillak; Velicia Diva Yolando; Roy Bartolomeus Oenunu; Wilhelmus Sandy Beoang; Yohanes Arman (Jurnal Relasi Publik, 2023)
Indonesia is an archipelagic country that has many outer islands which are directly adjacent to neighboring countries. Indonesia's outermost areas have high potential for marine resources so that they are used by Indonesian traditional fishermen as a source of income to support their families. BPS noted that there are 17,001 islands scattered throughout Indonesia. In preparing this article, the author used a normative juridical approach which was carried out through literature study by examining primary and secondary legal materials. Whereas for data analysis using qualitative juridical analysis that is descriptive based on principles, theories in international law. never protested the British claim of ownership of the sand islands. In 1974 the governments of Indonesia and Australia signed an MoU which stipulated that Indonesian traditional fishermen were permitted to fish. There are three important things that must be done by Indonesia-Australia, in order to get rid of fishing disputes by Indonesian traditional fishermen in Australia, namely strengthening national regulations, especially on the Exclusive Economic Zone maritime boundary agreement, secondly restoring the rights of traditional fishermen on sand islands. and the third is an agreement between the governments of Indonesia, Australia and Indonesia in setting sea boundaries.